PENGELOLAAN KUALITAS PEMBELAJARAN PKn MODEL KOOPERATIF TIPE TGT MENGGUNAKAN MEDIA AUDIOVISUAL PADA SISWA SMK - Wita Mahdalena (UNIVERSITAS BENGKULU, 2015)
This study aims to improve the management of the quality of citizenship learning with model cooperative TGT type. This research is a classroom action research through planning, action, observation, and reflection. The data source is a teacher, student, documentation, and field notes. Data collection techniques include test and non tes.Data analysis using descriptive statistics.The results showed that the skills of teachers increased from the first cycle, second cycle and third cycle. Number average score of student activity increased from the first cycle, second cycle andthird cycle as well as the classical completeness.Keywords: citizenship, cooperatice, TGT type